Wolf Hall and moral personhood - Hämäläinen, Nora Fiona Karolina (Sciendo, 2019)
Can a good man do evil things? This paper offers a moral philosophical reading of Hilary Mantel's novels Wolf Hall and Bring up the bodies, focusing on Mantel's fictional portrayal of Thomas Cromwell as a good person, in spite of his growing involvement in the dirty work of Henry VIII. The narrative resists interpretations of Cromwell as someone corrupted by power. It also thwarts attempts to read his deeds as results of a deficient capacity for sympathetic imagination, which has been a focalized moral flaw in contemporary moral philosophical discussions of literature. By thus resisting moralized readings of his character, the novels invite intensified attention to the complex dynamics of character and circumstance.
Wolf Hall and moral personhood
Keywords: ethics; philosophy and literature; character; Hilary Mantel; Wolf Hall; Bring up the Bodies; etika; filosofie a literatura; charakter; Hilary Mantel; Wolf Hall